2008
DOI: 10.1177/0884533608326060
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Considerations in Traumatic Brain Injury

Abstract: The provision of adequate nutrition support for patients with traumatic brain injury (TBI) has been a clinical challenge for decades. The primary and secondary injuries create unique metabolic derangements along with accompanying issues such as optimal timing and route of nutrition, appropriate fluid and electrolytes, drug administration, rehabilitation, and dysphagia. Enteral nutrition is clearly established as the preferential route of nutrition support for this population vs parenteral nutrition. There appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
91
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(96 citation statements)
references
References 115 publications
(218 reference statements)
1
91
0
2
Order By: Relevance
“…Patients manifesting post-TBI GI dysfunction have increased morbidity and longer periods of hospitalization; therefore, treatment modalities targeting prevention of GI dysfunction have important clinical implications (Cook et al, 2008;Kemp et al, 2008). Previously, we, along with others, have shown, in a mouse model, that TBI causes GI dysfunction characterized by increased intestinal permeability and marked mucosal injury, which was confirmed by intestinal histology Feighery et al, 2008;Hang et al, 2003).…”
mentioning
confidence: 85%
“…Patients manifesting post-TBI GI dysfunction have increased morbidity and longer periods of hospitalization; therefore, treatment modalities targeting prevention of GI dysfunction have important clinical implications (Cook et al, 2008;Kemp et al, 2008). Previously, we, along with others, have shown, in a mouse model, that TBI causes GI dysfunction characterized by increased intestinal permeability and marked mucosal injury, which was confirmed by intestinal histology Feighery et al, 2008;Hang et al, 2003).…”
mentioning
confidence: 85%
“…RTA formed 73.14% of the etiologies. Lyle et al 17 in their study of clinical course and outcome of 159 severe head injury patients in Australia found that majority were males with a ratio of 2.7:1 to females. Their mean age was 30 years and 74% were under 40 years with RTA constituting 65% of the etiological factors.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring of cerebral perfusion and oxygenation, which is discussed in subsequent sections, is particularly crucial in this scenario (Young et al 2010). Because of the brain's role in regulating metabolism, patients with severe traumatic brain injury demonstrate a number of metabolic derangements which ultimately result in systemic catabolism (Cook, Peppard, & Magnuson 2008). Adequate nutritional support is essential to forestall adverse consequences, including protein loss and immunocompromise (Sacks et al 1995).…”
Section: Principles Of Intensive Carementioning
confidence: 99%
“…Patients with severe TBI will require replacement of approximately 140% of their resting energy expenditure, though this requirement will be decreased somewhat in the setting of pharmacological paralysis or deep sedation. Protein requirements are estimated at about 1.5-2 grams/kg of protein (Cook, Peppard, & Magnuson 2008). Close monitoring is essential to ensure adequate supplementation and avoid complications such as hyperglycemia.…”
Section: Principles Of Intensive Carementioning
confidence: 99%